PENGARUH BAURAN PEMASARAN TERHADAP PENINGKATAN VOLUME PENJUALAN DI BEGOS (BEBEK GOYANG SULAWESI) KOTA KENDARI - Zainuddin, Muh. Zabir; M., Suyuti H.; Sari, Anggit Arum (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2020)
This study aims to determine the effect of marketing mix consisting of product, price, place, and promotion partially on sales volume increase in Begos in Kendari City, and to determine the effect of marketing mix consisting of product, price, place, and promotion simultaneously on sales volume increase in Begos in Kendari City. Methods used in this research are qualitative and quantitative.Data analysis tool used multiple linear regression using SPSS 20. The results of this study state that: simultaneously the marketing mix variable consisting of product, price, place, and promotion have a significant effect on sales volume increase in Begos in Kendari City. Product and place have a significant effect on sales volume increase in Begos in Kendari City. Price and promotion have no significant effect on sales volume increase in Begos in Kendari City.